Sustainability or performance? Ratings and fund managers’ incentives - Gantchev, Nickolay; Giannetti, Mariassunta; Li, Rachel (Journal of Financial Economics, 2024)
We explore how mutual fund managers and investors react when the tradeoff between a fund's sustainability and performance becomes salient. Following the introduction of Morningstar's sustainability ratings (the “globe” ratings), mutual funds increased their holdings of sustainable stocks to attract flows. Such sustainability-driven trades, however, underperformed, impairing the funds’ overall performance. Consequently, a tradeoff between sustainability and performance emerged. In the new equilibrium, the globe ratings do not affect investor flows and funds no longer trade to improve their globe ratings.